Coronary microvascular disease is associated with decreased nailfold capillary density in patients with ischemia and no obstructive coronary arteries. (3rd May 2023) - Sakalidis, A; Dimitriadis, K; Dri, I; Leontsinis, I; Mantzouranis, E; Ntalakouras, I; Iliakis, P; Vlachakis, P; Doundoulakis, I; Soulaidopoulos, S; Beneki, I; Mavroudis, A; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Existing data support that coronary microcirculation impairment is common in patients with angina pectoris without obstructive coronary artery disease. There are insufficient data in the literature regarding possible generalized microangiopathy in the above population. Purpose: The aim of this study is to evaluate whether patients with coronary microvascular dysfunction (CMD) compared to individuals without angina are characterized by a different level of capillary density in the nailfold capillary microscopy. Methods: We examined 21 patients [9 female, 39%, mean age: 61.2±9.9 years, mean office blood pressure (BP) : 139/86±18/10 mmHg] and 25 CMD patients (16 female, 64%, mean age : 57.9±4.8 years, average office BP: 127/77±18/10 mmHg). In the group of patients with chronic angina pectoris CMD was defined by a standardized systematic protocol in which coronary flow reserve (CFR) and index of microvascular resistance (IMR) were measured in the left anterior descending coronary artery using a temperature/pressure sensor-tipped guidewire. CMD patients were classified into 2 groups, the structural and the functional endotype, based on commonly used cut-offs (impaired CFR < 2.5, increased IMR ≥ 25). Functional CMD was defined as abnormal CFR in combination with normal IMR and structural CMD as abnormal CFR with abnormal IMR. In addition, the assessment of skin microcirculation was performed by capillaroscopy, a non-invasive technique to evaluate small vessels of the microcirculation in the nailfold, using stereomicroscope in all patients. Results: In CMD group, mean CFR and IMR were 1.6 ± 0.9 and 43.9± 30 IU, respectively. Of the 25 patients with abnormal CFR, 8 (32%) had normal IMR consistent with functional CMD endotype, and 17 (68%) had abnormal IMR consistent with structural endotype. Capillary density in patients with CMD was significantly decreased compared to that of asymptomatic participants (9 vs 10.86 vessels/mm, p=0.04). The difference in capillary density between the two groups was statistically significant after adjustment for multiple comparisons (p<0.05). No significant difference was found in body mass index, renal function, medical history of dyslipidemia, diabetes mellitus and smoking status between the two groups (p<0.05). Conclusion: Patients with CMD compared to individuals without angina are characterized by decreased nailfold capillary density. These results suggest that there is a correlation between microcirculatory impairment at the level of the coronary microcirculation and the peripheral vascular beds.